Prezydentury rządzące we współczesnym świecie - Nawracaj, Weronika (2023)
THE RULING PRESIDENCIES IN THE MODERN WORLDThe presidential system as a form of government inevitably makes one think about the American political system. This is not a wrong association, as any analysis of the American system involves presidentialism, which became its beginning and thus a point of reference. Nevertheless, ruling presidencies, i.e., the strong position of the head of state in the system, which is anchored in constitutional regulations and practice, are also present in other parts of the world, in a form that is far removed from the American original.The aim of the work is to show that the presidential system is neither uniform, as it is usually called, nor rigid, as shown in the system analysis presented in the paper. The rigidity of the division of powers ascribed to this formula of government seems to be one of the elements that construct an ideal type, which no political system can or is able to be in practice. The intention of the work is to show that ruling presidencies may occur in diverse variants of relations between the authorities, and thus the contemporary presidential system is undergoing a process that, in the author’s opinion, can be called an evolution. Depending on the state, its political history, genesis and characteristics, this evolution proceeds in a various directions, from the transformation of the classic ruling presidency into hyper-presidency (i.e., an absolutist presidency) to a strong presidency coupled with parliamentary elements.
Keywords: presidential system; president; ruling presidencies; constitution; United States of America; Russian Federation; South America; Cyprus